2020
DOI: 10.3389/fonc.2020.598107
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NAT10 Induces Apoptosis Associated With Enhancing Endoplasmic Reticulum Stress in Acute Myeloid Leukemia Cells

Abstract: N-acetyltransferase 10 (NAT10) has oncogenic properties in many tumors through its role in different cellular biological processes. NAT10 is also a potential biomarker in acute myeloid leukemia (AML); however, the mechanisms underlying NAT10’s contribution to disease states and the effect of targeting NAT10 as a therapeutic target remain unclear. NAT10 was found to be highly expressed in patients with AML, and increased NAT10 expression was associated with poor outcomes. Additionally, targeting NAT10 via the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 35 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…Remodelin is a small molecule inhibitor of N‐acetyltransferase 10 (NAT10) reported to decrease protein expression of NAT10 and its downstream targets 1–4 . Studies have shown Remodelin to correct the defect of laminopathic cells, reduce viral copies in human immunodeficiency virus (HIV) and reverse cancer progression 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Remodelin is a small molecule inhibitor of N‐acetyltransferase 10 (NAT10) reported to decrease protein expression of NAT10 and its downstream targets 1–4 . Studies have shown Remodelin to correct the defect of laminopathic cells, reduce viral copies in human immunodeficiency virus (HIV) and reverse cancer progression 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using Remodelin treated acute myeloid leukemia cell lines showed decreased antiapoptotic genes such as cyclin‐dependent kinase 2 ( CDK2), CDK4, cyclin D1 , and cyclin E, BCL2 , and an increase in proapoptotic genes such as p16 and p21 . Remodelin was also shown to affect the unfolded protein response pathway by altering IRE1, CHOP, and PERK protein expression 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,31,32]. As the only ac4C modi cation producer, NAT10 is signi cantly associated with the prognosis of several malignant tumours and potently promotes the tumour progression [30,[33][34][35][36][37][38][39]. High expression of NAT10 in hepatocellular carcinoma [30,37,39] and colorectal cancer [38] is associated with a worse prognosis in patients.…”
Section: Discussionmentioning
confidence: 99%